2019
DOI: 10.1080/13102818.2018.1555010
|View full text |Cite
|
Sign up to set email alerts
|

Biological characteristics and genome-wide sequence analysis of endophytic nitrogen-fixing bacteria Klebsiella variicola GN02

Abstract: The biological characteristics and genome-wide sequence analysis of highly efficient endophytic nitrogen-fixing bacteria Klebsiella variicola GN02 isolated from the roots of Pennisetum sinense Roxb. were studied by the combination of second-generation and third-generation sequencing techniques. The cell cultivation characteristics, microscopic morphological observation and infrared spectroscopic analysis of this GN02 strain were performed and its genome assembly, gene prediction and functional annotation, eggN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…SA187 genome includes dissimilatory nitrate reduction genes apart from genes coding for the nitrogenase enzyme (nifDHK). Klebsiella variicola GN02 and K. variicola DX120E genome hold numerous genes associated with nitrogen fixation, for example, nif gene cluster (nifHDK and nifLA), nitrogen metabolism-regulatory genes (ntrBC and glnD), and ammonium carrier gene (amtB) (Lin et al, 2012(Lin et al, , 2015Biaosheng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…SA187 genome includes dissimilatory nitrate reduction genes apart from genes coding for the nitrogenase enzyme (nifDHK). Klebsiella variicola GN02 and K. variicola DX120E genome hold numerous genes associated with nitrogen fixation, for example, nif gene cluster (nifHDK and nifLA), nitrogen metabolism-regulatory genes (ntrBC and glnD), and ammonium carrier gene (amtB) (Lin et al, 2012(Lin et al, , 2015Biaosheng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Research on sugarcane endophytic bacteria has been mostly focused on biological nitrogen fixing bacteria ( Trivedi et al., 2021 ). Bacteria of the genus Klebsiella belonging to the family Enterobacteriaceae stimulated plant growth via an array of direct and indirect mechanisms that are of increasing biotechnological interest due to their potential bio-inoculants for plant growth ( Lin et al., 2019 ; Medina-Cordoba et al., 2021 ). Carolina et al.…”
Section: Discussionmentioning
confidence: 99%
“…SA187 genome. The genomes of Klebsiella variicola GN02, K. variicola DX120E, Enterobacter roggenkampii ED5, and streptomyces chartreuses WZS021 also contain several nitrogen fixation-related genes, such as nif gene clusters, nifHDK, iscU , and nifLA ; nitrogen metabolism regulator genes, ntrBC and glnD ; and ammonia assimilation cycle gene, amtB (Lin et al, 2015 , 2019 ; Wang et al, 2019 ; Guo et al, 2020 ). In this study, DNDH-GDH, GS, and NR activities were examined with the inoculated strain DJ06, and the results showed that sugarcane nitrogen metabolism enzyme activities were changed after inoculation of the DJ06 strain.…”
Section: Discussionmentioning
confidence: 99%